Evidence supporting dissimilatory and assimilatory lignin degradation in Enterobacter lignolyticus SCF1 - DeAngelis, Kristen M.; Sharma, Deepak; Varney, Rebecca; Simmons, Blake A.; Isern, Nancy G.; Markillie, Lye Meng; Nicora, Carrie D.; Norbeck, Angela D.; Taylor, Ronald C.; Aldrich, Joshua T.; Robinson, Errol W. (Frontiers in Microbiology, 2013)
The anaerobic isolate Enterobacter lignolyticus SCF1 was initially cultivated based on anaerobic growth on lignin as sole carbon source. The source of the isolated bacteria was from tropical forest soils that decompose litter rapidly with low and fluctuating redox potentials, making it likely that bacteria using oxygen-independent enzymes play an important role in decomposition. We have used transcriptomics and proteomics to examine the increased growth of the anaerobic isolate Enterobacter lignolyticus SCF1 when grown on media amended with lignin compared to unamended growth. Proteomics revealed accelerated xylose uptake and metabolism under lignin-amended growth, and lignin degradation via the 4-hydroxyphenylacetate degradation pathway, catalase/peroxidase enzymes, and the glutathione biosynthesis and glutathione S-transferase proteins. We also observed increased production of NADH-quinone oxidoreductase, other electron transport chain proteins, and ATP synthase and ATP-binding cassette (ABC) transporters. We detected significant lignin degradation over time by absorbance, and also used metabolomics to demonstrate increased xylose utilization in lignin-amended compared to unamended growth. Our data shows the advantages of a multi-omics approach, where incomplete pathways identified by genomics were completed, and new observations made on coping with poor carbon availability. The fast growth, high efficiency and specificity of enzymes employed in bacterial anaerobic litter deconstruction makes these soils useful templates for improving biofuel production.